2012
DOI: 10.1089/scd.2011.0413
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Cord Blood-Derived Mesenchymal Stromal Cells for the Prevention of Acute Graft-Versus-Host Disease in a Xenogenic Mouse Model

Abstract: Human mesenchymal stromal cells (MSCs) have been successfully utilized for the treatment of refractory graft-versus-host disease (GvHD). Despite the large number of in vitro and in vivo models developed for clarifying their immunomodulatory properties, the mechanism of action of MSCs remains elusive and their efficacy controversial. Here, we tested the ability of cord blood-derived MSCs to alleviate the symptoms of GvHD induced by the injection of human peripheral blood mononuclear cells into NOD/SCID/γc(-) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…This was effectively demonstrated by the ability of a single low dose (0.5 Â 10 6 ) of rapamycintreated UC-MSCs to significantly inhibit the onset of xenogeneic GVHD. The same number of untreated cells had no apparent effect, and, even a dose of 2 Â 10 6 , similar to that used in other studies [37,38], showed only a trend toward greater survival. Whereas rapamycin alone has been used for prevention of solid-organ transplant rejection and aGVHD in mice transplant models [30,31], doses of 3 Â 50 mg were insufficient in our experiments, as was a single dose of 50 ng that we calculate to be the approximate amount of drug introduced by the pretreated MSC (data not shown).…”
Section: Discussionsupporting
confidence: 57%
“…This was effectively demonstrated by the ability of a single low dose (0.5 Â 10 6 ) of rapamycintreated UC-MSCs to significantly inhibit the onset of xenogeneic GVHD. The same number of untreated cells had no apparent effect, and, even a dose of 2 Â 10 6 , similar to that used in other studies [37,38], showed only a trend toward greater survival. Whereas rapamycin alone has been used for prevention of solid-organ transplant rejection and aGVHD in mice transplant models [30,31], doses of 3 Â 50 mg were insufficient in our experiments, as was a single dose of 50 ng that we calculate to be the approximate amount of drug introduced by the pretreated MSC (data not shown).…”
Section: Discussionsupporting
confidence: 57%
“…Previously, Cao et al, showed that when ex vivo expanded Treg were co-transferred with peripheral blood lymphocytes into the spleens of NOD/SCID mice, GvHD was prevented and survival significantly enhanced 29 . This model has also been used to study the GvHD-ameliorating effects of mesenchymal stem cells 30 . Similar to our findings, Hippen et al 4 , have previously shown that ex vivo expanded CB derived Tregs, expanded using both CD3/28 beads or cell based techniques, are able to inhibit xenogenic GvHD in a NK-deficient C57BL/6 Rag - / - , γc - / - mouse model 4 .…”
Section: Discussionmentioning
confidence: 99%
“…These cells are clinically attractive, as they show very low immunogenicity, and they can induce immunosuppression in vitro and in vivo [15], and available data from clinical trials indicate that they are safe and have shown some efficacy in ameliorating GvHD and autoimmune disease outcome in patients [2,[4][5][6][26][27][28][29][30]. However, their mechanism of action is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Human CB-MSCs were obtained from CB mononuclear cells, and immortalized as previously described [15]. This cell line, which retains both the phenotype and differentiation capacity typical of freshly isolated MSCs, can be safely used for in vivo injection due to their characteristic cell-contact-induced growth arrest.…”
Section: Msc Isolation and Culturementioning
confidence: 99%
See 1 more Smart Citation